Midaq Alley by Naguib Mahfouz:an analytical appraisal based on Mohd. Affandi Hassan’s theoretical framework,Persuratan Baru - Ungku Maimunah Mohd Tahir, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
Midaq Alley by the Nobel Laureate Naguib Mahfouz has been hailed as a powerful and faithful portrayal of the working classes of Cairo society. In analyzing the text, the article has availed itself of a homegrown analytical framework, Persuratan Baru, which is capable of transcending specificities of not only areas and regions but also cultures and religions. Persuratan Baru argues that a story is a vehicle for purposes of developing discourses and disseminating ideas. Against the backdrop of this concern, the article contends that Midaq Alley prioritises story over knowledge, at the same time as its narrative space is given over to details, embellishments and an absence of a moral centre.Thus, whilst Midaq Alley may come across as a powerful realistic novel, it nevertheless falls short of the key concern that stories develop discourses and disseminate knowledge,congruent with the Islamic literary tradition of using the pen to teach.